2-Pyridone-directed CuII-catalyzed general method of C(sp2)-H activation for C-S, C-Se, and C-N cross-coupling: easy access to aryl thioethers, selenide ethers, and sulfonamides and DFT study - Pati, Tanmay K.; Molla, Sabir Ali; Ghosh, Narendra Nath; Kundu, Mrinalkanti; Ajarul, Sk; Maity, Pradip; Khamrai, Uttam; Maiti, Dilip K. (Journal of Organic Chemistry, 2024)
We have demonstrated N-substituted 2-pyridones as an N,O-directing group for selective C(sp(2))-H-activated thiolation, selenylation, and sulfonamidation of ortho C-H bonds of benzamides. This method utilizes a cost-effective Cu(II)-salt catalyst instead of precious metal catalysts, achieving high yields, including gram-scale synthesis and excellent functional group tolerance. We applied this protocol to access 30 different compounds with high yields, demonstrating thiolation of fluorine-substituted benzamides as well. Density functional theory (DFT) calculations support the mechanism, including acetate-supported concerted metalation deprotonation (CMD) steps and the unique role of dimethyl sulfoxide (DMSO) solvent. The facile synthesis of pharmaceutically important sulfonamides and other compounds highlights the method's potential in chemistry and medicinal chemistry.